History of Friedrich II of Prussia $1 (BVolume 12s - Carlyle, Thomas, 1795-1881 (Salt Lake City, UT : Project Gutenberg, 2008)
"History of Friedrich II of Prussia $1 (BVolume 12" by Thomas Carlyle is the twelfth volume of a monumental biography published between 1858 and 1865. This ambitious work chronicles the life of Frederick the Great, consuming thirteen years of Carlyle's life and requiring two research trips to Germany, including visits to twelve battlefields. The result captivated readers with its vivid characterizations and battle scenes, earning praise from Emerson, Roosevelt, and countless others who recognized it as a masterpiece of literary genius$1 (Ba work where every page pulses with wit, insight, and historical narrative. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/History_of_Friedrich_II._of_Prussia,_Called_Frederick_the_Great
Release date is 2008-06-16
Produced by D.R. Thompson and David Widger
Keywords: Social problems; Frederick II, King of Prussia, 1712-1786; Prussia (Germany) -- History -- Frederick II, 1740-1786